2021
DOI: 10.3390/ma14030690
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction and Ion Bombardment Effects of Plasma Radicals on Optoelectrical Properties of SnO2 Thin Films via Atomic Layer Deposition

Abstract: In this study, the effect of radical intensity on the deposition mechanism, optical, and electrical properties of tin oxide (SnO2) thin films is investigated. The SnO2 thin films are prepared by plasma-enhanced atomic layer deposition with different plasma power from 1000 to 3000 W. The experimental results show that plasma contains different amount of argon radicals (Ar*) and oxygen radicals (O*) with the increased power. The three deposition mechanisms are indicated by the variation of Ar* and O* intensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…When the power increased to 60 and 80 W, oxygen ion bombardment caused severe structural damage or dispersion. This result is similar to those of other studies [ 17 , 22 ]. Thus, high-quality composite perovskite films can be prepared with lower oxygen plasma powers below 20 W.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…When the power increased to 60 and 80 W, oxygen ion bombardment caused severe structural damage or dispersion. This result is similar to those of other studies [ 17 , 22 ]. Thus, high-quality composite perovskite films can be prepared with lower oxygen plasma powers below 20 W.…”
Section: Resultssupporting
confidence: 93%
“…The strongest absorbance of the films was obtained at 20 W due to the removal of the excess impurities on their surface. With power in the range of 40 to 80 W, the absorbance gradually decreased owing to the degradation of MAPbI 3 induced by the bombardment of oxygen ions at high power [ 17 ]. Another possible reason could be that the film surface suffered from the damage of oxygen ion bombardment, and this caused structure dispersion, similar to what observed in studies on plasma engineering [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the surface of the perovskite films was treated with the oxygen plasma at 20 to 80 W. It can be observed that the strongest absorbance of the films was at 20 W, because the excess ligands and impurities were removed from the surface. However, the absorbance gradually decreased in the power range of 40 to 80 W due to the degradation of MAPbI 3 caused by high-power oxygen ion bombardment [ 15 ]. Figure 2 b shows the photoluminescence (PL) results of the pure MAPbI 3 film and MAPbI 3 films doped with CsPbI 3 QDs with and without oxygen plasma treatment at 20 W. The PL intensity of the MAPbI 3 film doped with CsPbI 3 QDs was drastically enhanced compared to that of pure MAPbI 3 film due to the Cs ion exchange process [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, an excessive supply of oxygen plasma with power over 20 W caused the formation of bonds between carbon, lead and oxygen. This effect leads to the degradation of MAPbI 3 [ 10 , 15 ], and therefore the mobility dropped from 6.06 × 10 3 to 1.08 × 10 4 cm 2 /V s . Compared to the untreated film, the carrier concentration of the treated MAPbI 3 film was also enhanced.…”
Section: Resultsmentioning
confidence: 99%